An Analysis of Conversational Maxims in Dr. Oz Talk Show - Pulungan Nababan; Zainuddin Zainuddin (State University of Medan, 2014)
ABSTRACT This study deals with an analysis of conversational maxims in Dr. Oz talk show. The objectives of the study are (1) to find out the types of maxim that used in Dr. Oz talk show, (2) to find out the most dominant type of maxim used in Dr. Oz talk show, and (3) to give the reasons why the most type of maxim used in Dr. Oz talk show by using Grice’s theory of Cooperative Principle. The study was conducted by qualitative method. The date were obtained from the video and transcription of two episodes of “Dr. Oz” program, namely “Celine Dion and Dr.Oz One on One” and “GMO Foods: Are They Dangerous to Your Health?”. The data were analyzed by applying qualitative content analysis. The findings indicated that there are four types of maxim occurred in the Dr. Oz talk show, namely: maxim of quantity 28 utterances (47,45%), maxim of quality6 utterances (10,26%), maxim of relevant 14 utterances (23,72%), and maxim of manner 11 utterances (18,64%). The dominant type of maxim appeared is maxim of quantity occurs with 28 utterances (47,45%) from 59 utterances. The reasons of the dominant type of maxim appeared because the information of interviewees was informative as required from the interviewer. Keyword :Pragmatics, Cooperative principle, maxims, Talk show